Fenomena Jokes Seksis Mahasiswa Sebagai Bentuk Normalisasi Pelecehan Seksual Secara Verbal - Allyssa Farisa Yasmine; Chazizah Gusnita (Dinasti Research, 2024)
This research discusses the phenomenon of students' sexist jokes as a form of normalization of verbal sexual disclosure. The purpose of this research is to find out how students can normalize sexual verbal displays wrapped in sexist jokes. The research approach used is qualitative descriptive research in order to obtain comprehensive and in-depth data. Primary data in this research was obtained from the results of interviews conducted with 6 (six) informants, all of whom were students at Bdudi Luhur University. Meanwhile, secondary data is obtained from books, scientific works, theses, online articles, and others that are relevant to the research used as a reference in writing. The results of interviews conducted with informants were explained by researchers using neutralization theory introduced by Sykes and Matza (1957). The results obtained from this research are that male students as perpetrators of sexist jokes normalize the act of sexual disclosure using the neutralization techniques of The Denial of Responsibility: in telling sexist jokes the perpetrator only follows other friends; The Denial of Injury: finds the perpetrator that the victim enjoyed the sexist joke he made; The Denial of Victim: the perpetrator will make sexist jokes at victims who speak poorly and look bad; The Condemnation of The Condemners: the victim still enjoys and does not feel hurt by the jokes they make so they will not think about the views and input of other people; Appeal to Higher Loyalties: the perpetrator also believes that sexist jokes are a sign of closeness in a friendship.